Social suffering and return migrations: a conceptual proposal - Parella, Sònia (2019)
This article highlights how social suffering, conceived of as a  manifestation of social oppression and injustice incorporated into the individual,  has attributes that are evident in the different stages of the migratory return, which are marked by transnational and multilocal processes. To this  end, the VIA Model – composed of the analytical axes of vulnerability,uncertainty and assistance – allows for  the description, interpretation and  analysis of social suffering during the return process through a multilevel  analysis that connects the perceptions and experiences of the actors with  structural inequalities.